Erythematous ixodic tick-borne borreliosis in children over twenty-year monitoring period - A. P. Pomogaeva; O. V. Obidina (LLC "Diagnostics and Vaccines", 2019)
We generalized the observed results obtained in the last twenty years from patients at the age of 1 to 14 years suffered from acute erythematous ixodic tick-borne borreliosis. Clinical characteristics of erythematous ixodic tick-borne borreliosis have not changed dramatically over twenty years. Key manifestations in children remain erythema at the site of a tick bite, fever, and regional lymphadenitis. These signs allow us to diagnose nosological form of the disease.